PENGARUH MODIFIKASI TERHADAP KARAKTERISTIK TEPUNG OPA (Dioscorea esculenta L.) TERMODIFIKASI : STUDI KEPUSTAKAAN - Fahmiyasin, Muhammad; Wahyuni, Sri; Khaeruni, Andi (Jurnal Sains dan Teknologi Pangan, 2019)
ABSTRACT                     This review aimed to investigate the effect of the modification of the yam flour on the characteristics of the produced yam flour. In addition, this review also aimed to determine the composition of yam flour starch. Modification process of Yam flour was done to improve the characteristics of flour produced. Modified yam flour also produced better flour properties than ordinary yam flour. The modification process can be done in several ways including through fermentation modification and using acid. The results of the review showed that the modification process (fermentation) was proven to improve the characteristics of yam flour better than using acid. Modified yam flour had the potential to substitute wheat flour in food processing. Keywords: yam flour, modification, characteristics of yam flour. ABSTRAKReview ini bertujuan untuk melihat pengaruh perlakuan modifikasi tepung opa terhadap karakteristik tepung opa yang dihasilkan. Selain itu, review ini juga bertujuan untuk mengetahui komposisi pati tepung opa. Proses modifikasi tepung opa dilakukan untuk untuk memperbaiki karakteristik tepung yang dihasilkan. Tepung opa termodifikasi juga menghasilkan sifat tepung yang lebih baik dari tepung opa biasa. Proses modifikasi dapat dilakukan melalui beberapa cara diantaranya adalah melalui modifikasi secara fermentasi dan menggunakan asam. Hasil review menunjukkan bahwa proses modifikasi dengan fermentasi terbukti dapat memperbaiki karakteristik tepung opa lebih baik daripada menggunakan asam. Tepung opa termodifikasi memiliki potensi untuk mensubtitusi tepung terigu pada pengolahan pangan. Kata kunci: Tepung opa, modifikasi, karakteristik tepung opa.